ESTUDO DO ENVELHECIMENTO DE MISTURAS EM CONCRETO ASFÁLTICO COM DIFERENTES TIPOS E TEORES DE LIGANTES - Bock, Andre L.; Hartmann, Diego A.; Budny, Jaelson; Treichel, Diego; Rozek, Thiago; Specht, Luciano P. (Salão do Conhecimento, 2013)
Resumo